Divergent effects of monomethyl branched-chain fatty acids on energy metabolism and insulin signaling in human myotubes - Parmeshwar Bajirao Katare; Ragna H. Tingstad; Sivar T. Beajani; Jørgen Pasjkurov Indseth; Vibeke H. Telle-Hansen; Mari C.W. Myhrstad; Arild C. Rustan; Lars Eide; Oliwia Witczak; Vigdis Aas (Journal of Lipid Research)
Branched-chain fatty acids (BCFAs) are predominantly saturated fatty acids with one or more methyl branches on the carbon chain, typically found in dairy products and measured in micromolar concentrations in human plasma. The biological function of BCFAs in humans remains ill-defined, but a relationship between circulating BCFAs and cardiometabolic health has been suggested. The objective of this study was to evaluate the impact of BCFAs on energy metabolism in human myotubes. The results revealed distinct effects of BCFAs. 12-Methyltetradecanoic acid (12-MTD) increased glucose uptake and glycogen synthesis, while 13-methyltetradecanoic acid (13-MTD), 14-methylhexadecanoic acid (14-MHD), and 15-methylhexadecanoic acid (15-MHD) increased oleic acid uptake and 13-MTD and 15-MHD oleic acid oxidation, indicating a more general stimulatory effect on fatty acid than glucose metabolism. Interestingly, the same BCFAs, 13-MTD, 14-MHD, and 15-MHD, appeared to reduce insulin-stimulated glycogen synthesis. Insulin-stimulated phosphorylation of IRS1 was not apparent after exposure to 12-MTD, 13-MTD, and 15-MHD, whereas insulin-stimulated phosphorylation of Akt was unchanged by BCFAs. Incorporation of [14C]leucine into lipids was affected, as 13-MTD increased the total lipid content, and 12-MTD altered the distribution of lipid classes. Metabolic flux analysis indicated that 14-MHD stimulated extracellular acidification. The effects of BCFAs might involve increased mRNA expression of pyruvate dehydrogenase kinase 4. In conclusion, the study demonstrates that different BCFAs have distinct effects on energy metabolism in myotubes, 12-MTD mainly affect glucose metabolism, while 13-MTD, 14-MHD, and 15-MHD modulated oleic acid metabolism. These data suggest that some BCFAs might have therapeutic applications by improving energy metabolism.